Semiautomatic quantification of 3D Histone H3 phosphorylation signals during cell division in Arabidopsis root meristems - Kelemen, Adrienn (The New phytologist, 2025)
© 2025 The Author(s). New Phytologist © 2025 New Phytologist Foundation.